Analisis self-confidence terhadap hasil belajar matematika siswa SMK - Rida Adhari Yanti; Ii Faidhotuniam; Muhammad Yasin (Universitas Sultan Ageng Tirtayasa, 2022)
This research aimed to determine the impact of students' self-confidence on their mathematical learning outcomes. This study is a qualitative research that uses survey methods. A total of 269 respondents from three schools, such as Serang City 7 State Vocational School, Plus Pakuhaji Vocational School, and Mutiara Insan Nusantara Vocational School, who were majoring in computer and network engineering, motorcycle engineering and business, accounting, sharia banking, and office management, made up the study's population of all vocational students in the cities of Serang and Tangerang. The cluster sampling approach is used to select the sample. To determine the correlation between four indicators of learning outcomes and students' levels of self-confidence, Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis was performed on the results of three daily math examinations. The findings revealed that: (1) Student self-confidence significantly influenced student learning outcomes, accounting for 70.9%; (2) The indicator of student self-confidence that had the highest effect was on the self-confidence aspect, amounting to 86.3%; (3) The effect of student learning outcomes is on the r-square value, which is similar to that of student learning outcomes, but the highest is on the value of the second daily test, which is equal to 88.1%.